Urban waterfront landscape: the social impact on urban waterfront landscape / Salina Mohamed Ali and Abdul Hadi Nawawi - Mohamed Ali, Salina; Nawawi, Abdul Hadi (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2010)
Urban waterfronts began as commerce centers. They survived on trade. Whether a city or town was located on an inland river or an ocean port, its main focus was on the transportation of goods via water. In the 18 th , 19 th and early 20 th centuries, as the industrial revolution began to take shape and shipping and manufacturing began to become powerful sectors in economic growth, waterfronts too moved forward. Urban waterfront redevelopment phenomena have been largely ignored in the developing world until recently. In the last decade, developing countries have been seeking to revive their historic port cities, in diverse contexts ranging from post-colonialism and globalization to culture revival and tourism development. In Malaysia, waterfront landscape is still new and can be identified as a park for leisure entertainment. Waterfront in Malaysia has attracted attention from domestic and overseas researchers only recently. Studies of urban waterfront cases in Malaysia and the introduction of foreign experiences of successful urban waterfront redevelopment cases emerged in Malaysia in the 1990s.